Genetic diversity analysis of selected Capsicum annuum genotypes based on morphophysiological, yield characteristics and their biochemical properties - Ridzuan, Raihana; Rafii, Mohd Y.; Mohammad Yusoff, Martini; Ismail, Siti Izera; Miah, Gous; Usman, Magaji G. (John Wiley & Sons, 2019)
Background: Assessment of the different desirable characters among chili genotypes has expanded the effective selection for crop improvement. Identification of genetically superior parents is important in assortment of the best parents to develop new chili hybrids.